A Building Condition in Influencing the Walkable Environment in Traditional Street of Melaka Historical City - Haslina Ja’afar, Nor; ., . (International Journal of Engineering and Technology, 2018)
Street as a social arena plays an essential role in representing the character of a city, thus it is important to create a street with a friendly walkable environment. Therefore, this study is aimed to determine the heritage building conditions that contribute towards the walkable environment in traditional streets in Melaka Historical City, Malaysia. The places comprised of Jalan Tukang Besi, Jalan Tukang Emas, and Jalan Tokong. Questionnaire survey, in-depth interview with the street users, observation, and document review on historical significant were conducted to achieve the objective of this study. The findings demonstrated that a good building condition is essential in order to encourage a street with walkable environment. The findings inform designers and planners of the importance to preserve our heritage buildings in street design and development.Â